2002
DOI: 10.1002/jos.96
|View full text |Cite
|
Sign up to set email alerts
|

Approximation algorithms for shop scheduling problems with minsum objective

Abstract: SUMMARYWe consider a general class of multiprocessor shop scheduling problems, preemptive or non-preemptive, with precedence constraints between operations, with job or operation release dates, and with a class of objective functions including weighted sums of job, operations and stage completion times. We present a general approximation method combining a linear programming relaxation in the operation completion times, with any algorithm for the makespan version of these problems without release dates. If the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 29 publications
(32 reference statements)
0
45
0
Order By: Relevance
“…Queyranne & Sviridenko [15] showed that an approximation algorithm for the above mentioned problems that produces a schedule with makespan a factor O(ρ) away from the lower bound lb can be used to obtain a O(ρ)-approximation algorithms for other objectives, including the sum of weighted completion times. The only known inapproximability result is by Hoogeveen, Schuurman & Woeginger [7], who showed that F || C j is NP-hard to approximate within a ratio better than 1 + for some small > 0.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Queyranne & Sviridenko [15] showed that an approximation algorithm for the above mentioned problems that produces a schedule with makespan a factor O(ρ) away from the lower bound lb can be used to obtain a O(ρ)-approximation algorithms for other objectives, including the sum of weighted completion times. The only known inapproximability result is by Hoogeveen, Schuurman & Woeginger [7], who showed that F || C j is NP-hard to approximate within a ratio better than 1 + for some small > 0.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An interesting recent development is the work of Queyranne and Sviridenko (1999), in which they consider approximation algorithms for shop-scheduling problems with a minimal sum of job completion times objective. Their main result is the following: If there exists a polynomial-time algorithm for a class of multiprocessor job-shop problems that guarantees a makespan no larger than times the trivial lower bound (the so-called congestion-dilation bound), then they describe a polynomial-time algorithm for minimizing the weighted completion time that is within a factor of 8 of the optimum.…”
Section: Related Workmentioning
confidence: 99%
“…Their algorithm involves use of the approximation scheme for the makespan objective. Note that the polynomial-time approximation schemes for the makespan objective do not always satisfy the hypothesis of their statement: The work of Queyranne and Sviridenko (1999) requires a makespan guarantee that is within a factor of of a lower bound, not the optimal makespan itself. In fact, recent results of Hoogeveen et al (1998) show that the job-shop problem with the objective of minimizing weighted completion time does not have a polynomial-time approximation scheme unless P = NP .…”
Section: Related Workmentioning
confidence: 99%
“…Kim [15] proved that the problem is NP-hard when edge lengths are the same and showed that Graham's list scheduling algorithm [7], when guided by an optimal solution to a linear programming relaxation, gives an approximation ratio of 3. When edges have arbitrary lengths there are several constant factor approximation algorithms [5,15,20] with the best approximation guarantee being 5.03 [5].…”
Section: Introductionmentioning
confidence: 99%
“…This problem is a special case of the data migration problem [5]. Open shop scheduling problem has been studied in [3,12,19,20].…”
Section: Introductionmentioning
confidence: 99%